2017
DOI: 10.1590/1519-6984.06715
|View full text |Cite
|
Sign up to set email alerts
|

Biological properties of disturbed and undisturbed Cerrado sensu stricto from Northeast Brazil

Abstract: The aim of this study was to measure soil microbial biomass and soil surface fauna in undisturbed and disturbed Cerrado sensu stricto (Css) from Sete Cidades National Park, Northeast Brazil. The following sites were sampled under Cerrado sensu stricto (Css) at the park: undisturbed and disturbed Css (slash-and-burn agricultural practices). Total organic and microbial biomass C were higher in undisturbed than in disturbed sites in both seasons. However, microbial biomass C was higher in the wet than in the dry … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 28 publications
2
4
0
Order By: Relevance
“…There are 22 faunal groups present in the different management systems studied (Table 3). There were changes in the soil fauna variables evaluated as a function of the soil management system, corroborating other works in the savanna piauiense (Santos et al, 2016;Araújo et al, 2017).…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…There are 22 faunal groups present in the different management systems studied (Table 3). There were changes in the soil fauna variables evaluated as a function of the soil management system, corroborating other works in the savanna piauiense (Santos et al, 2016;Araújo et al, 2017).…”
Section: Resultssupporting
confidence: 89%
“…The groups Araneae and Pseudoscorpionida showed higher occurrence in the native savanna area. Similar result on the density of the Araneae group was observed by Araújo et al (2017), working in preserved and unpreserved native savanna area. The predominance of the Araneae group in FA may be associated with the accumulation of leaves in the reference area, as this greater amount of leaves provides greater heterogeneity in the burlap microhabitat.…”
Section: Resultssupporting
confidence: 85%
See 1 more Smart Citation
“…The effects on the diversity of soil fauna have been the main focus of scientific investigations regarding the substitution of forest by monoculture systems, mainly regarding loss of habitat quality and its ecological and evolutionary consequences. Some studies have already shown the differences in the diversity, composition of fauna species in different ecosystems resulting from the process of fragmentation of forests in equilibrium, such as the Caatinga (Araújo et el., 2010), Mata de Cocais (Nunes et al, 2012), Mata Atlântica (Pereira et al, 2013), Cerrado (Araújo et al, 2017) and areas with distinct floristic domains (Nunes et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Notwithstanding, in spite of the importance of the PNSC, the work done so far is related to botanical (Oliveira et al, 2010), soil chemical and microbiological (Araújo et al, 2017) and geomorphological aspects (IBDF, 1979). In this sense, information on soil invertebrates is extremely relevant, since it can provide data on nutrient cycling and the regulation of primary productivity in these environments (Bustamante et al, 2004).…”
Section: Introductionmentioning
confidence: 99%